Transcranial Direct Current Stimulation Alleviates Neurovascular Unit Dysfunction in Mice With Preclinical Alzheimer’s Disease - Luo, Yinpei; Yang, Hong; Yan, Xiaojing; Wu, Yaran; Wei, Guoliang; Wu, Xiaoying; Tian, Xuelong; Xiong, Ying; Wu, Guangyan; Wen, Huizhong (Frontiers in Aging Neuroscience, 2022)
Neurons, glial cells and blood vessels are collectively referred to as the neurovascular unit (NVU). In the Alzheimer's disease (AD) brain, the main components of the NVU undergo pathological changes. Transcranial direct current stimulation (tDCS) can protect neurons, induce changes in glial cells, regulate cerebral blood flow, and exert long-term neuroprotection. However, the mechanism by which tDCS improves NVU function is unclear. In this study, we explored the effect of tDCS on the NVU in mice with preclinical AD and the related mechanisms. 10 sessions of tDCS were given to six-month-old male APP/PS1 mice in the preclinical stage. The model group, sham stimulation group, and control group were made up of APP/PS1 mice and C57 mice of the same age. All mice were histologically evaluated two months after receiving tDCS. Protein content was measured using Western blotting and an enzyme-linked immunosorbent assay. The link between glial cells and blood vessels was studied using immunofluorescence staining and lectin staining. The results showed that tDCS affected the metabolism of Aβ; the levels of Aβ, amyloid precursor protein (APP) and BACE1 were significantly reduced, and the levels of ADAM10 were significantly increased in the frontal cortex and hippocampus in the stimulation group. In the stimulation group, tDCS reduced the protein levels of Iba1 and GFAP and increased the protein levels of NeuN, LRP1 and PDGRFβ. This suggests that tDCS can improve NVU function in APP/PS1 mice in the preclinical stage. Increased blood vessel density and blood vessel length, decreased IgG extravasation, and increased the protein levels of occludin and coverage of astrocyte foot processes with blood vessels suggested that tDCS had a protective effect on the blood-brain barrier. Furthermore, the increased numbers of Vimentin, S100 expression and blood vessels (lectin-positive) around Aβ indicated that the effect of tDCS was mediated by astrocytes and blood vessels. There was no significant difference in these parameters between the model group and the sham stimulation group. In conclusion, our results show that tDCS can improve NVU function in APP/PS1 mice in the preclinical stage, providing further support for the use of tDCS as a treatment for AD.